Тайна тринадцати апостолов: [роман] / Наталья Александрова - Александрова Наталья Николаевна (Артефакт & Детектив, 2018)
Экземпляры: (20190419) / Инвентарный номер: 40822 / Цена: 237.30 / Сис.шифр: Р2 / Авт.знак: А 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6